Gambaran Pengetahuan dan Sikap Mahasiswa Program Profesi Dokter Gigi Terhadap Intervensi Minimal Kedokteran Gigi - Gadara Alifah Nur Vega; Ade Prijanti Dwisaptarini (Fakultas Kedokteran Gigi Universitas Trisakti, 2021)
Minimal intervention dentistry (MID) is a modern approach to the management of dental caries. The philosophy of professional care in minimal intervention dentistry can be defined as focusing on the initial symptom, early detection, immediate treatment on a micro scale, followed with minimally invasive and patient-friendly treatment to restore damages caused by dental caries. Objective: The aim of this study was to describe the knowledge and attitude about minimal intervention dentistry among dental students in clinical years and postgraduate dental students in the faculty of dentistry, Universitas Trisakti. Method: This research was conducted using descriptive observational cross-sectional design on dental students in clinical years and postgraduate dental students. The data were collected using a questionnaire. Result: Total of 129 respondents were involved. Almost all research subjects could answer the questionnaire correctly regarding knowledge with 71,93% of dental students in clinical years and 84,38% of post graduate dental students. In attitude section, have a positive attitude with 74,28% of dental students in clinical years and 87,5% of post graduate dental student agree with the concept of minimal dentistry intervention, while the attitude in daily practice of dental students in clinical years answered that they had never do minimum intervention procedure with 32.7% and post graduate dental student answered sometimes do that procedure with 32.1%. Conclusion: Dental students in clinical years show good knowledge and positive attitude, but it doesn’t affect their attitudes in daily practice, whereas residency doctors have good knowledge, attitude, and practices that include into the positive category of minimal interventions dentistry.